PRINCIPLE OF HUMANIZATION AND PSYCHOLOGIZATION OF PEDAGOGICAL MANAGEMENT AS A BASIS PERSONAL-ORIENTED IMPLEMENTATIONS TRAINING DURING THE PROFESSIONAL PROCESS TRAINING OF PEDAGOGICAL STAFF - H.B. Shtelmakh; O.B. Polishchuk (Academy of Cognitive and Natural Sciences, 2007)
The article deals with the principle of humanismation and psycholigation of pedagogical management during professional training.